An item response theory analysis of a measure of complicated grief. - Boelen PA; Hoijtink H (Death Studies, 2009)
Item response theory modeling was applied to the data of 1,321 bereaved individuals who completed the Dutch version of the Inventory of Complicated Grief-Revised (ICG-R)-a 29-item self-report measure of complicated grief (CG). The authors aimed to examine the information that each of the ICG-R items contributes to the measurement of overall CG severity and to detect possible differences between subgroups of mourners in the way CG items are endorsed. Findings showed that items differed in their ability to distinguish individual differences in CG severity. Items that discriminated best between low and high CG were 'feeling numb,' 'feeling that the future holds no meaning or purpose,' and 'unable imagining life being fulfilling without the lost person.' Items were reasonably well dispersed across the range of CG severity. There was little evidence of differential item functioning between gender groups and victims of violent vs. non-violent loss.